Multiple Osteolytic Lesions Causing Hypercalcemia: A Rare Presentation of Acute Lymphoblastic Leukemia. (17th July 2017) - Mahmood, Khalid; Ubaid, Muhammad; Taliya Rizvi, Syeda
Abstract : Acute lymphoblastic leukemia is characterized by unchecked proliferation of malignant lymphoblasts which replaces the normal bone marrow culminating in anemia due to red blood cells inadequacy as well as in easy bruising/bleeding secondary to insufficient platelets production. Even the white blood cells which are produced excessively are immature and abnormal. ALL is the most common hematological malignancy in children. Most commonly, patients present with lymphadenopathy, recurrent infections, bleeding, fatigue, and bone pains. Bone pains, often particularly involving long bones, occur in about 21–38% of cases and are due to overcrowding of bone marrow with malignant cells. Vast majority of children with ALL have thrombocytopenia and/or anemia with a normal or mildly elevated white blood cells count with the presence of lymphoblasts on peripheral smear. About 50% of children present with bleeding while about 75% of patients have platelet count 100, 000/microL. Visceromegaly is not uncommon but osteolytic lesions and hypercalcemia are rather uncommon. We present a 22-year-old gentleman with generalized fatigue and bone pains without visceromegaly. There was severe hypercalcemia with normal parathyroid levels but multiple osteolytic lesions. Peripheral smear showed anemia without blasts, whereas a bone marrow biopsy revealed > 30% blasts with interspersed CD 10 positive cells.